Problematika Pengajaran Bahasa Arab Di Madrasah Aliyah - Agus Supriadi; Akla Akla; J. Sutarjo (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
This study aimed to analyze the problematics of teaching Arabic students in Islamic Senior High School. The method in this research was qualitative with a case study approach. This research was conducted at Islamic Senior High School Raudlatul Hidayah Ma'arif Nahdlatul Ulama 03 Mengandungsari. Research samples were 30 students of grade XI. Data collection methods in this study were observation and interviews. Data analysis techniques used descriptive qualitative analysis. The results showed that teaching Arabic in Islamic Senior High School included two main problems: linguistic and nonlinguistic problems. Linguistic problems were problems experienced by students during the learning process, and these problems were still related to parts of the language component. Linguistic problems included three main issues that became problematic in Arabic teaching, and they were phoneme problems (ashwat), vocabulary problems (mufrodat), and grammatical problems (qowaid/ nahwu/ tarkib). At the same time, nonlinguistic problems were problems which were not part of the language element. Such as teacher taught students, lack of motivation towards students, learning media, facilities and infrastructure that were still inadequate during the Arabic learning process.